Interwar Printed Mass Media of Small Lithuanian Towns: Non-Ideological Small-Scale Newspapers Published by School Students - Hall, Lina (Lietuvos istorijos studijos, 2025)
The article investigates non-ideological small-scale newspapers published by high school students. This phenomenon has essentially never been noted in historiography. The research covers the main ideas of these minor newspapers, their financial and organizational background, the main topics to be developed, the key points and core values. In this research, these small-scale papers are interpreted as a means of local mass media, as a peculiar reflection of their period, a curious outcome at a crossroads of specific political and socio-cultural circumstances which renders the unique perspective of ‘everyday history’, as manifested by children and adolescents, and also a whirlpool of the public space of the communities with the developing self-expression and interpersonal relationships.